Formation of a new working class in regions with development poles: Manaos (Amazonia Brazil) and Chubut (Patagonia, Argentina), in the 1960s and 1970s - Pérez Álvarez, Gonzalo (2017)
This article analyzes the formation of a new working class in the development poles that were established in Patagonia and Amazonia during the 1960s and 1970s. The growth of industry required the influx of workers to these areas, but this does not imply that there were no workers there initially. However, the scale of the transformation that took place led to the development of what can be called a new class. This class included migrants from various areas who had few traditions and experiences in common and a history conditioned by industrialization dependent on state subsidies. We analyze how each working class grew and the forms of struggle and organization they developed. The study is based on a literature survey, journalistic sources, census data, and interviews with workers. Studying this process contributes to an understanding of similar dynamics in other countries, where experiences of subsidized industrialization were also implemented.